Activation of Heteroallenes COxS2–x (x = 0–2): Experimental and Theoretical Evidence of the Synthetic Versatility of a Bulky Guanidinato SmII Complex. Issue 6 (1st February 2016) - Castro, Ludovic; Mills, David P.; Jones, Cameron; Maron, Laurent
Abstract: A joint experimental/theoretical (DFT) study of the activation of heteroallenes CO x S2– x ( x = 0–2) by [Sm(Giso)2 ] Giso – = [(ArN)2 CNCy2 ] –, Cy = cyclohexyl, Ar = 2, 6‐diisopropylphenyl is reported. All heteroallenes are reduced in a different manner. Indeed, while activation of CS2 yields a bimetallic CS2 coupled product through C–S bond formation, CO2 forms an oxalate complex through C–C bond formation. This subsequently undergoes CO2 insertion into one of its Sm–N bonds. Finally, COS activation is predicted to yield a dithiocarbonate complex, through the formation of an intermediate sulfido complex [(Giso)2 Sm(µ‐S)Sm(Giso)2 ]. Therefore, [Sm(Giso)2 ] is a very versatile reagent, since it is a rare example of a complex that allows formation of several activation products involving valence isoelectronic substrates. This is rationalized by DFT calculations, and the latter emphasizes both the lack of kinetic stability of CS vs. CO and the high thermodynamic stability of the oxalate. Abstract : A combined experimental/DFT study of the activation of CO x S2– x ( x = 0–2) by [Sm(Giso)2 ] is reported. Activation of CS2 yields a bimetallic CS2 coupled product. CO2 forms an oxalate complex through C–C bond formation, which then undergoes CO2 insertion into one of its Sm–N bonds. COS activation is predicted to yield a dithiocarbonate complex, through the formation of an intermediate sulfido complex.